Effects of prolonged unemployment and reemployment on psychological and physical health - Galić, Zvonimir (Array, 2008)
Summary: The purpose of the present study was to explore the impact of prolonged unemployment and reemployment on both psychological and physical health over a period of more than two years. In a three-way longitudinal survey of initially unemployed persons in Croatia, we examined the self-assessed physical and mental health, captured by the SF-36 Health Survey, as a group of unemployed persons moved into employment or remained unemployed. The results confirmed that only psychological health depends on the participant’s employment status, while physical health wasn’t related to prolonged unemployment or (re)employment